DEMYSTIFYING CLOUD COMPUTING AND VIRTUALIZATION: A TECHNICAL OVERVIEW - Rajesh Basa (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
This comprehensive article explores the transformative impact of cloud computing and virtualization on modern information technology landscapes. It delves into the fundamental concepts, key characteristics, and service models of cloud computing, highlighting its rapid market growth and widespread adoption across industries. The article examines virtualization as the enabling technology behind cloud computing, discussing its core concepts, benefits, and market projections. It further investigates the practical applications of these technologies in enterprise IT infrastructure, software development, disaster recovery, and edge computing, supported by real-world examples and statistical data. The article concludes by exploring future trends in the field, including serverless computing, multi-cloud strategies, and the integration of AI and machine learning, providing insights into the evolving nature of cloud and virtualization technologies and their potential to drive innovation and efficiency across various sectors.